Guidelines for the management and treatment of periodic fever syndromes Cryopyrin-associated periodic syndromes (cryopyrinopathies - CAPS) - Terreri, Maria Teresa R.A.; Bernardo, Wanderley Marques; Len, Claudio Arnaldo; da Silva, Clovis Artur Almeida; de Magalhães, Cristina Medeiros Ribeiro; Sacchetti, Silvana B.; Ferriani, Virgínia Paes Leme; Piotto, Daniela Gerent Petry; Cavalcanti, André de Souza; de Moraes, Ana Júlia Pantoja; Sztajnbok, Flavio Roberto; de Oliveira, Sheila Knupp Feitosa; et al. (Elsevier, 2016)
Objective: To establish guidelines based on cientific evidences for the management of cryopyrin associated periodic syndromes. Description of the evidence collection method: The Guideline was prepared from 4 clinical questions that were structured through PICO (Patient, Intervention or indicator, Comparison and Outcome), to search in key primary scientific information databases. After defining the potential studies to support the recommendations, these were graduated considering their strength of evidence and grade of recommendation. Results: 1215 articles were retrieved and evaluated by title and abstract; from these, 42 articles were selected to support the recommendations. Recommendations: 1. The diagnosis of CAPS is based on clinical history and clinical manifestations, and later confirmed by genetic study. CAPS may manifest itself in three phenotypes: FCAS (mild form), MWS (intermediate form) and CINCA (severe form). Neurological, ophthalmic, otorhinolaryngological and radiological assessments may be highly valuable in distinguishing between syndromes; 2. The genetic diagnosis with NLRP3 gene analysis must be conducted in suspected cases of CAPS, i.e., individuals presenting before 20 years of age, recurrent episodes of inflammation expressed by a mild fever and urticaria; 3. Laboratory abnormalities include leukocytosis and elevated serum levels of inflammatory proteins; and 4. Targeted therapies directed against interleukin-1 lead to rapid remission of symptoms in most patients. However, there are important limitations on the long-term safety. None of the three anti-IL-1β inhibitors prevents progression of bone lesions.
Keywords: Autoinflammatory syndromes; Chronic infantile neurologic; Cutaneous and articular; Familiar cold autoinflammatory; Guidelines; Muckle-Wells syndrome; Syndrome